Does Labor Union Utility Increase Workers' Organizational Commitment and Job Satisfaction? The Moderating Role of Labor Union Membership. (November 2018) - Choi, Intae
The purpose of this study is to address whether labor union members' organizational commitment and job satisfaction are more influenced by labor union utility than those of nonunion employees. This study uses data from the Korean Labor and Income Panel Study published by the Korea Labor Institute. The study's methodology employs panel data regression analysis. The findings are that labor union utility increases workers' organizational commitment and job satisfaction and that these effects are positively greater for labor union members than nonunion employees.